2018
DOI: 10.3389/fimmu.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytochromes P450 in Infection

Abstract: Cytochromes are expressed in many different tissues of the human body. They are found mostly in intestinal and hepatic tissues. Cytochromes P450 (CYPs) are enzymes that oxidize substances using iron and are able to metabolize a large variety of xenobiotic substances. CYP enzymes are linked to a wide array of reactions including and O-dealkylation, S-oxidation, epoxidation, and hydroxylation. The activity of the typical P450 cytochrome is influenced by a variety of factors, such as genus, environment, disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 51 publications
(86 reference statements)
0
94
0
Order By: Relevance
“…Arachidonic acid is released from membrane phospholipids by phospholipases, and can be converted into pro-inflammatory prostaglandins via specific prostaglandin synthases and oxidases. Alternatively, it can be metabolized by Cyp (cytochrome P450) enzymes and lipoxygenases to anti-inflammatory hydroxyeicosatetraenoic acids (HETEs) and epoxyeicosatrienoic acids (EETs) 26,27 . As shown in Fig.…”
Section: Plasminogen Treatment Of Radiation-induced Wounds Results Inmentioning
confidence: 99%
“…Arachidonic acid is released from membrane phospholipids by phospholipases, and can be converted into pro-inflammatory prostaglandins via specific prostaglandin synthases and oxidases. Alternatively, it can be metabolized by Cyp (cytochrome P450) enzymes and lipoxygenases to anti-inflammatory hydroxyeicosatetraenoic acids (HETEs) and epoxyeicosatrienoic acids (EETs) 26,27 . As shown in Fig.…”
Section: Plasminogen Treatment Of Radiation-induced Wounds Results Inmentioning
confidence: 99%
“…These selected genes are, VIPR1, mainly located on plasma membrane and PPP1R14A majorly located on nucleus and cytoskeleton were moderately found to be involved in virus infections like HIV-1 and influenza as reported by an in-vitro study and an in-silico phosphoproteomics study in human macrophages respectively [51-53]. CYP1A1 was recently reported to be involved in many virus infections especially hepatitis B and hepatitis C virus [54-56]. One such report superficially uncovers the induction of CYP1A1 in presences of PM 10 [57].…”
Section: Discussionmentioning
confidence: 99%
“…CYP proteins are known to metabolize a wide array of small molecules such as fatty acids, alkanes, and xenobiotic drugs. Recent studies have shown their involvement in microbial infections 85,86 . In our analysis, five CYP members (2A4, 2A5, 2E1, 4A10, and 4A14) were found to be significantly down-regulated in day-7 kidneys compared to day-2.…”
Section: Discovery-based Studies Recapitulate Signature Proteins For mentioning
confidence: 99%
“…For example, the expression of Cyp4a10 was dramatically increased after acute infection (at day 2) and declined back to the basal level at chronic stage (at day 7) ( Figure 6C). It has been noted that CYP enzymes can be selectively regulated in different states of inflammation by a multitude of cytokines released after infection or inflammation 85 . In hepatic and extrahepatic tissues, chronic inflammation is usually associated with downregulation of CYP enzymes 85 .…”
Section: Discovery-based Studies Recapitulate Signature Proteins For mentioning
confidence: 99%
See 1 more Smart Citation